Retrospective Analysis of EEG Patterns in the Patients Referred for EEG at a Tertiary Care Hospital in Western Nepal - Bagban, Mohammad Ainuddin; Belbase, Mohan; Khan, Tanveer Ahmed; Khanal, Sudesh; Siddiqui, Saharoj (Journal of Nepalgunj Medical College, 2025)
Introduction: Electroencephalography is a non-invasive neurophysiological test that records electrical activity in the brain. It can help in the diagnosis and monitoring of various clinical conditions, like seizures and sleep disorders. Extensive research on electro encephalographic patterns is scarce, especially in Western Nepal. The study will also help to avoid the consequences of misinterpreting different waveforms.Aims: To analyze various normal and abnormal electroencephalographic wave patterns.Methods: This was an observational retrospective study analyzing electroencephalographic reports of the patients referred for electro encephalography in the Department of Psychiatry, Nepalgunj Medical College Teaching Hospital, Kohalpur, from January 2023 to December 2024. Total 290 patients who underwent a 20-minute electroencephalography, meeting the study criteria were selected. Descriptive statistics were used to analyze demographic data and electroencephalographic findings.Results: Out of 290 patients, 57.9% were male. The most common condition referred for electroencephalographic evaluation was seizure disorder (51%), followed by psychogenic non-epileptic seizure (24.1%). Patients with normal electro encephalographic waveforms were 79%, whereas 21% had abnormal electroencephalographic waveforms. Among normal variant waveforms, wicket waves were seen more frequently (7.42%), particularly in children and adolescents. Polyspike waves were the most frequently observed (47.54%) among the abnormal waveforms.Conclusion: The EEG waveforms were normal in most cases, while a few had abnormal EEG findings. The normal variants must not be misinterpreted as epileptiform discharges to avoid the consequences of misdiagnosis.